(3TQM GdMeGSI CHj JeGes - (3jMji Hf Ydj Hf GdMSf Hf ehSi Hf HSWGe GdNWjH GdJHQjRj GddZhj , CHh RcQjG , J (B502 (3g` s; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3aJi YjT ai eYQhag HYO ehJg ceG cGf HYO GdSHjd eLQGg eQJYkG s
(3BNQgG (B:s
(3Ef JSCdi aGdeLO ZjQ GdHOjY bO Md ai Jje heNRhe BNQ TQM cJGH GdMeGSI s
(3GdTQM GdUZjQs
(3gPG GdLRA ef GdfSNI GdKGdKI faSgG GdLRA GdChdGdSYjOjg Jhfc (B126 (3COH YQHis
(3HChdgG Jedc HJGQjN (B1054 (3g`s
(3fSNI QGHYI s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs